2012
DOI: 10.1371/journal.pone.0051813
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Internalization Mechanism and Intracellular Trafficking of Filamentous M13 Phages Displaying a Cell-Penetrating Transbody and TAT Peptide

Abstract: Cellular internalization of bacteriophage by surface-displayed cell penetrating peptides has been reported, though the underlying mechanism remains elusive. Here we describe in detail the internalization mechanism and intracellular trafficking and stability of filamentous M13 phages, the cellular entry of which is mediated by surface-displayed cell-penetrating light chain variable domain 3D8 VL transbody (3D8 VL-M13) or TAT peptide (TAT-M13). Recombinant 3D8 VL-M13 and TAT-M13 phages were efficiently internali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
57
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(63 citation statements)
references
References 40 publications
6
57
0
Order By: Relevance
“…The inability of cytotransmabs to internalize into HSPG-deficient cells demonstrated that their cellular uptake initiated via HSPGs as cell surface receptors, like the parent VLs, 16,17 though the precise HSPG molecule remains to be identified. HSPGs commonly serve as internalizing receptors for many macromolecules, including CPPs, anti-DNA antibodies, polycation-nucleic acid complexes, viruses, and growth factors.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The inability of cytotransmabs to internalize into HSPG-deficient cells demonstrated that their cellular uptake initiated via HSPGs as cell surface receptors, like the parent VLs, 16,17 though the precise HSPG molecule remains to be identified. HSPGs commonly serve as internalizing receptors for many macromolecules, including CPPs, anti-DNA antibodies, polycation-nucleic acid complexes, viruses, and growth factors.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 The presence of exogenous heparin, which is a close structural homolog of HS, significantly inhibited the cellular internalization of TMab4 and HuT4 (Fig. 3B).…”
Section: Endocytic Mechanisms Underlying Cytotransmab Internalizationmentioning
confidence: 92%
See 2 more Smart Citations
“…CXCR4 differs from CCR5 in that it is degraded through lysosomal pathways after agonist stimulation, whereas CCR5 is recycled back to the cell surface (59 -61). Because the fate of the internalized phage is largely dictated by the trafficking properties of the displayed protein (62), it is probable that phage particles displaying CXCL12 agonists were efficiently degraded and therefore not available for recovery. In cases where the receptor traffics through degradative pathways, using lysosomal inhibitors may permit selection of internalizing receptor agonists in future phage display experiments.…”
Section: Selected Cxcl12 Variants Bind Both Ackr3 and Cxcr4 With Highmentioning
confidence: 99%